1990
DOI: 10.1111/j.1440-1681.1990.tb01321.x
|View full text |Cite
|
Sign up to set email alerts
|

INHIBITION OF ENDOTHELIAL NITRIC OXIDE BIOSYNTHESIS BY N‐NITRO‐l‐ARGININE

Abstract: 1. The actions of N-nitro-L-arginine (NOLA) on the release of nitric oxide (NO) from arterial endothelial cells was studied in rat isolated thoracic aortic rings and by bioassay of NO derived from cultured bovine aortic endothelial cells. 2. NOLA (3-10 mumol/L) caused concentration-dependent inhibition of acetylcholine-induced relaxation of phenylephrine-contracted rat aortic rings, which is dependent on the release of NO from the endothelium. The inhibitory actions of NOLA could be prevented by pre- and co-in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0

Year Published

1991
1991
1995
1995

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(19 citation statements)
references
References 20 publications
2
17
0
Order By: Relevance
“…These amounts of dilation with these two concentrations of adenosine are comparable to those reported by other researchers. 21 Application of either 100 iimol/L L-NAME or 50 /xmol/L L-NA failed to attenuate the dilation observed by either dose of adenosine (Fig 2). These data suggest that application of L-NAME or L-NA at these concentrations does not, through some nonspecific mechanism, impair the ability of pial arterioles to dilate.…”
Section: L-name L-na and Adenosine-induced Pial Arteriolar Dilationmentioning
confidence: 82%
“…These amounts of dilation with these two concentrations of adenosine are comparable to those reported by other researchers. 21 Application of either 100 iimol/L L-NAME or 50 /xmol/L L-NA failed to attenuate the dilation observed by either dose of adenosine (Fig 2). These data suggest that application of L-NAME or L-NA at these concentrations does not, through some nonspecific mechanism, impair the ability of pial arterioles to dilate.…”
Section: L-name L-na and Adenosine-induced Pial Arteriolar Dilationmentioning
confidence: 82%
“…L-NNA inhibits the biosynthesis of NO in endothelial cells (Moore et al, 1990;Dubbin et al, 1990) and increases arterial pressure in anaesthetized rats . We have now shown that in the anaesthetized greyhound L-NNA increases arterial pressure and causes constriction of the left circumflex coronary artery despite the increase in distending pressure.…”
Section: Discussionmentioning
confidence: 99%
“…The finding that NO is synthesized in the endothelium from L-arginine (Palmer et al, 1988) led to the discovery of L-arginine analogues which potently and specifically inhibit the synthesis of end helium-derived NO both in vitro and in vivo. NO biosynthesis can be inhibited by N0-monomethyl-L-arginine (L-NMMA, Palmer et al, 1988) and N-nitro-L-arginine (L-NNA, Moore et al, 1990;Dubbin et al, 1990). Both of these agents increase arterial pressure in rats (Gardiner et al, 1990;Zambetis et al, 1990) and L-NMMA reduces forearm blood flow in human volunteers (Vallance et al, 1989), constricts a variety of vascular beds in the conscious rat (Gardiner et al, 1990) and causes coronary vasoconstriction in rabbit isolated hearts (Amezcua et al, 1989).…”
Section: Introductionmentioning
confidence: 99%
“…For the endothelial cell consti tutive enzyme, NG-nitro-L-arginine (NOLA or NOARG) appears more potent than the NG-monomethyl analogue [55,56], and the methyl ester (L-NAME) of NOLA is more soluble in aqueous media. N G-amino-L-arginine and N-imino-L-omithine are also more potent than L-NMMA on the endothelial NO synthase [20].…”
Section: Physiological Roles In Cardiovascular Functionmentioning
confidence: 99%